Integrasi Sejarah Matematika Pada Materi Phytagoras - Samosir, Katrina; Mulita, Bunga Aulia Syafira; Ritonga, Fahmi Fauzan; Mawaddah, Fiha; Br Surbakti, Juli Agina; Simanullang, Sri Antika (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to enhance students' learning motivation through the integration of mathematical history in the teaching of the Pythagoras Theorem. Based on national data, approximately 35% of junior high school students have not achieved the minimum numeracy competency. One strategy to improve students' understanding and motivation is by integrating the history of mathematics into learning. The research employs a literature study method to evaluate the impact of this approach. The results indicate that integrating the history of mathematics provides deeper context, boosts students' motivation by up to 11%, and fosters the development of critical thinking skills. This study recommends history-based teaching as a tool to strengthen conceptual understanding and the relevance of mathematics in everyday life